The impact of hydrostatic pressure on the result of physiological measurements in various coronary segments. (25th November 2020) - Uveges, A; Tar, B; Jenei, C.S; Agoston, A; Czuriga, D; Papp, Z; Csanadi, Z; Koszegi, Z.S
Abstract: Background: The effect of hydrostatic pressure on physiological intracoronary measurements is usually ignored in the daily clinical practice. Purpose: To investigate the effect of resting Pd/Pa (distal/aortic pressure) and FFR (fractional flow reserve) adjustment based on the calculation of hydrostatic pressure gradient between the coronary orifice and the pressure wire sensor. Methods: 41 FFR measurements (between 0.7 and 0.9) were selected. The difference in height of the orifice and the sensor was defined in cm on the basis of 3D coronary reconstruction. The resting Pd/Pa and FFR were adjusted by subtracting the pressure gradient from the distal pressure. Measurements were also performed from 2D lateral projections for each coronary segment visible (n=305). Results: In case of the left anterior descending artery (LAD), each segment was located higher (proximal: –13.69±5.4; middle: –46.13±6.1; distal: –56.80±7.7 mm), whereas for the circumflex (CX), lower (proximal: 14.98±8.3; distal: 28.04±6.3 mm) compared to the orifice. In case of the right coronary artery (RCA), the distance from the orifice was much less (proximal: –6.39±2.9; middle: –6.86±7.0; distal: 17.95±6.6 mm). The posterolateral (PL) and posterior descending (PD) branches of the distal RCA were located lower than the orifice (PL: 29.65±6.1; PD: 17.53±6.6 mm). The effect of these distances on pressure ratios at 100 Hgmm aortic pressure was between −0.044 and 0.023. After correction, values of 11 and 5 patients (27% and 12%) stepped the 0.92 Pd/Pa and 0.80 FFR cut-off values, respectively. There was a strong correlation between the 3D and 2D methods (r=0.98; p<0.001). Conclusion: The clinical implementation of hydrostatic pressure calculation should be considered during intracoronary pressure measurements. A correction for this parameter may become crucial in case of borderline significant coronary artery stenosis, especially in distal coronary artery segments. Funding Acknowledgement: Type of funding source: Public grant(s) – EU funding. Main funding source(s): Άron Üveges was supported by the EFOP-3.6.2-16-2017-00006 project. The project is co-financed by the European Union and the European Social Fund.